Case report: Transcatheter aortic valve replacement in a large bicuspid anatomy using the XL-Myval 32 mm - Elkoumy, Ahmed; Terkelsen, Christian J.; Abdelshafy, Mahmoud; Ellert-Gregersen, Julia; Elzomor, Hesham; Thim, Troels; Serruys, Patrick W.; Soliman, Osama; Nissen, Henrik (Frontiers in Cardiovascular Medicine, 2022)
Transcatheter aortic valve replacement (TAVR) is a recommended intervention in a selected population with severe aortic stenosis (AS). Bicuspid aortic valve (BAV) anatomy has been categorized as unfavorable anatomy for TAVR, due to multiple considerations, like the exclusion from randomized trials in addition, to the challenging and unpredictable anatomy. The anatomical constraints of BAV include the large anatomy of the annulus, sinuses of Valsalva and aorta (aortopathy), in addition to the significant calcifications of the device landing zone. Most of commercial transcatheter heart valves (THV) have an upper limit of the annulus dimensions and area in which the device can be implanted safely without significant oversizing. Myval-XL THVs (Meril Life Sciences Pvt. Ltd, India) are balloon-expandable valves (BEV) which developed with two new sizes of 30.5, and 32mm, aiming to treat patients with large annulus dimensions and exceeding the upper limit of the ordinary device sizing matrix. This case series report is describing TAVR using the XL-Myval 32mm THV in three European patients with symptomatic severe bicuspid aortic stenosis with significant calcifications and large annular dimensions exceeding the limits of the other THVs.